The rhetorical effect of multiple Quranic readings - Ayad Hashem Al-Marei; Dr. Mahdi Nasseri; Dr. Rasoul Dehqan-Zad (Journal of College of Education, 2024)
In Islam, al-Qirāʼah (pl. al-Qirāʼāt; literally ’recitations or readings’) refers to the ways or fashions that the Quran, the holy book of Islam, is read or recited. The Holy Qur’anic texts are considered a source of sciences in general, and a source of rhetoric in particular, because the Holy Qur’an has baffled Arabs and non-Arabs with its rhetorical texts that challenged the people of its time and every time. In this regard, the multiple Quranic readings are considered one of the miraculous rhetorical images represented by deletion, substitution, advancement and delay. The deletion of some words by some readers, and their inclusion by others, did not cause confusion in the text, but rather the same meaning was intended by both readings. Thus, the substitution of words in the different readings represented a miraculous rhetorical image, since the reading was a general image, and what was substituted for it was a detailed image of the same meaning. Likewise, the advancement of some words and their delay in others created another rhetorical image due to showing specialization, importance, or expressing glorification, or advancement of the tangible over the rational, and other rhetorical reasons for advance.